Pengujian Validitas Konstruk Kriteria Kecanduan Internet - Helly P. Soetjipto (Jurnal Psikologi, 2005)
This research is used to explore the  internet addiction concept which developed by Young who used  the  internet  consumer  subject  in Yogyakarta. 124 subjects (63 male a and  61 females) within 14‐35 years old, most of them were students, only 3 subjects who have worked. They catagorized as existing user  because   they had the criteria mentioned by Grohol (1999). Confirmatory  factor analysis became the basic for  construct  validity  testing. AMOS  fifth version (student version) was used to analyze the data. There are 2  factors which was tested  in structural equation model, they are main factor and additional factor.  The main factor consists of  5 items and additional   factor consists of 2 items. The result showed that structural equation model did not have the weakness which called Heywood Case,  because  there was  1  factor which consists of only 2  items. There are 2 modification suggested. The first modification model has discrepancy  index 9.782 (p>0.05) and the  second modification model  has  11.  452 (p>0.05). Keywords: construct validity,  internet addiction